PENGARUH PELATIHAN DAN PENGEMBANGAN TECHNICAL SKILL TERHADAP KINERJA KARYAWAN (STUDI PADA KARYAWAN PRODUKSI WELDING PT. MCDERMOTT INDONESIA-BATAM) - Zhafirah Widya Nurina; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study aims to determine the effect of training and development technical skills on employee performance partially and simultaneously. This study uses a questionnaire as a tool for collecting data distributed to 70 respondents to production employees have received training and technical skills development of PT. McDermott Indonesia Batam. The data is then processed using descriptive analysis and statistical analysis using SPSS 17.0 by conducting validity tests, reliability tests, simple linear regression analysis, multiple linear analysis, analysis of determination (R2) and hypothesis testing by testing t test (partial) and F test (simultaneous)The results showed that the first hypothesis testing was training for employee performance, t count (6,605)> t table (1,995), meaning that training had a significant effect on employee performance. Second, technical skill development is t count (6,371)> t table (1,995), meaning that technical skill development has a significant effect on employee performance. The results of the F test count (44,806)> F table (3,13), meaning that training and technical skill development simultaneously have a significant effect on employee performance. Keywords: Training, Technical Skill Development, Employee Performance